الاستغلال الامثل للوقت وتأثيره في انتاجية العاملين بالدوائر الحكومية : دراسة ميدانية لعام 2005 - أحلام معيوف الشماع (PROSPECTIVE RESEARCHES, 2023)
This study tackles the general and real social problem which is the suffering of all people when they attend to government offices which suffer from the problem of moral Hazarals, such as, corruption, barbarity, and wasting time. The people in the third world don't Like to visit the government offices because their document are either lost or late. This research tries to shed light on this problem, using the collective Samples from the government offices. The aim of this study is to shed light on those person working in the government offices, how shoed use the time efficiency. The research has come up with some conclusions such as: the effective planning is absent because of the absence of government observation on the official’s performance, in addition to the instability of the time of work. This study advises each the company and the government to follow the new control system helps the worker and protects them. In the same time it makes people focus on how to use the general position efficiency as a vary important job to complete the government duty not only the quick one.